Potential of Steroidal Alkaloids in Cancer: Perspective Insight Into Structure–Activity Relationships - Huang, Ying; Li, Gen; Hong, Chong; Zheng, Xia; Yu, Haiyang; Zhang, Yan (Frontiers in Oncology, 2021)
Steroidal alkaloids contain both steroidal and alkaloid properties in terms of chemical properties and pharmacological activities. Due to the outstanding biological activities as alkaloids and similar pharmacological effects to other steroids, steroidal alkaloids receive special attention in anticancer activity recently. Substituted groups in chemical structure play markedly important roles in biological activities. Therefore, the effective way to obtain lead compounds quickly is structural modification, which guided by structure-activity relationship (SAR). This review presents the SAR of steroidal alkaloids and anticancer, including pregnane alkaloids, cyclopregnane alkaloids, cholestane alkaloids, C-nor-D-homosteroidal alkaloids and bis-steroidal pyrazine. A summary of SAR could powerfully help to design and synthesis more lead compounds.